Insights on the Mesembryanthemum forsskalii phenotype and study of the effects of several exogenous plant growth regulators via plant tissue culture - Sumayah I. Alsanie (BMC Plant Biology)
Abstract Background Samh (Mesembryanthemum forsskalii, M. cryptanthum) belongs to Aizoaceae family and is found in northern Saudi Arabia, primarily in desert or dry shrubland habitats. M. forsskalii is characterized by several nutritional and medicinal benefits. This study aimed to explore the phenotypic features of M. forsskalii and investigate the impact of exogenous plant growth regulators (PGRs) on this species using tissue culture techniques. Different auxin (naphthalene acetic acid (NAA), 2,4-dichlorophenoxyacetic acid (2,4-D) and indole butyric acid (IBA) in addition cytokinin (benzyl amino purine (BA), and kinetin (Ki) treatments were used. Results The phenotypic features of M. forsskalii included being decumbent to erect, with many terete succulent branches covered by epidermal bladder cells. Plant size determines its branching type, phyllotaxis, and inflorescence. Large plants have trichotomous branching; the two lower nodes have opposite decussate leaves; and compound dichasia. The flowers are pedicellate, perigynous, and have single, tricorporate pollen grains. Additionally, M. forsskalii has taproots, which differs from what was reported for M. forsskalii in previous studies in that it has fibrous roots. A 98% response rate was seen when the receptacle was used as an initiated explant. Adding BA to the MS medium also showed a significant increase in the size of the shoot system area and the number of roots. as well as the combined Ki + 2,4-D treatment had a significant effect on the callus volume. The callus color ranged from yellowish green to brown, and compact and rooty calli (callus cells differentiated into root hairs) were observed. Conclusions This study investigated the phenotypic features of M. forsskalii (samh), and its micropropagation that had not been previously reported in the literature. Its branching type, phyllotaxis, and inflorescence were described. The flowers are pedicellate, and the pollen grains are single, tricorporate, and oblate. M. forsskalii has taproots, which differs from what was reported for M. cryptanthum (M. forsskalii) in previous studies in that it has fibrous roots. Therefore, the difference in the type of root may be an indication that the variety found in the Al-Jouf area is different than the previous varieties. This study was the first to examine the impact of exogenous PGR on M. forsskalii under tissue culture conditions. Based on the results of this study, the use of 2 mg/ml BA for M. forsskalii micropropagation and the combination of IBA and 2,4-D for callus induction experiments are recommended. Further molecular research on M. forsskalii is also recommended.